ZASTOSOWANIE KOMÓREK ROZRODCZYCH I ZARODKÓW W PROCEDURZE MEDYCZNIE WSPOMAGANEJ PROKREACJI - Kaczan, Damian (Zeszyty Prawnicze, 2016)
The Use of Reproductive Cells and Embryos in Medically Assisted Procreation Summary The article discusses the use of reproductive cells and embryos in medically assisted procreation in Poland, which is regulated by the Polish Treatment of Infertility Act (Ustawa o leczeniu niepłodności). The article is divided into six sections. In the first section the author explains why he has chosen to study this subject and the scope of the examination. In the second he explains the normative meaning of the key concepts for further consideration: the procedure of medically assisted procreation, the reproductive cell, the embryo, the donor, and the donor of the embryo. In the third section he presents the general provisions applicable in medically assisted procreation as one of the therapies used in Poland to treat infertility. The fourth and fifth sections are devoted to the recommendations and contraindications respectively for the undertaking of medically assisted procreation. In the sixth section the author assesses the new Polish act on medically assisted procreation and calls for its fundamental amendment or repeal.